EDS analysis of gutta-percha cones disinfected by 1% and 2.5% sodium hypochlorite solutions - Carvalho, Alessandra Sverberi; Leal, Flávia Martins; Vasconcelos, Rafaela Andrade; Junqueira, Rafael Binato; Gonçalves, Simone Helena Ferreira (Brazilian Dental Science, 2015)
Objective: To evaluate the effects of 1% and 2.5% sodium hypochlorite (NaOCl) solutions at different periods of time on the composition of gutta-percha cones using Energy Dispersive Spectroscopy (EDS). Material and Methods: 110 master gutta-percha points were divided into 3 control groups and 8 experimental groups. Cones were immersed in 1% and 2.5% NaOCl for 30 minutes, 6, 12, 24 hours. Then, composition of the samples was analyzed by EDS. Statistical analysis was performed using the ANOVA and Tukey tests (p<0.05). Results: There was an increase of oxygen in experimental groups, and decrease of zinc when NaOCl was used, concentration and time-dependent. Conclusions: The disinfection with NaOCl solution causes alterations in the composition of gutta-percha cones. These modifications in gutta-percha structure might change important characteristics, increasing the risk of leakage and consequently failure of root canal treatment.